Peran Guru Terhadap Disiplin Belajar Siswa dalam Mata Pelajaran Akidah Akhlak di MI Al-Hikmah Kota Pagar Alam - Pramisty, Dea Mareta; Kalsum, Nyayu (Yayasan Amanah Nur Aman, 2025)
This study aims to describe the role of teachers in the attitude of student learning discipline in Akidah Akhlak subjects at MI Al-Hikmah Pagar Alam City. Teachers are not only tasked with delivering material, but also as role models in shaping student character, including in terms of learning discipline. Disciplinary attitude is one of the important factors that support the success of the learning process, especially in Islamic values-based character education. The method used in this research is a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation of grade V teachers and students. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results showed that teachers have a strategic role in shaping student learning discipline, through providing motivation, exemplary, and consistent application of rules. Supporting factors for success include the support of the school environment, good communication between teachers and students, and parental involvement. Meanwhile, inhibiting factors include students' low awareness of the importance of discipline and lack of control from the environment outside the school.